Post-partum Rupture of liver Haematoma in a Patient with HELLP Syndrome: A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Hepatic rupture from haematomas is a rare complication of HELLP syndrome. Subcapsular liver haematoma has been reported in less than 2% of cases complicated by HELLP syndrome. It is associated with increased perinatal & neonatal mortality. A careful aggressive & multidisciplinary approach is crucial for saving the lives of patients with hepatic rupture. Most liver haematomas with subcapsular rupture occur antenatally but also in the post-partum period. This report presents a 37-year-old woman with a hepatic rupture from subcapsular liver haematoma secondary to HELLP syndrome diagnosed during post-partum period.Bangladesh J Obstet Gynaecol, 2021; Vol. 36(2): 135-137